Poor uptake of fluorodeoxyglucose in positron emission tomography-computed tomography scan for intraocular choroidal melanoma in Asian Indian Eyes - Rahul Sharma; Parag Shah; Venkatapathy Narendran (World Journal of Nuclear Medicine)
Fluorodeoxyglucose (FDG) positron emission tomography-computed tomography (PET-CT) scan is fast becoming a very useful tool in diagnosing and staging of several malignancies that affect the human body. We report three cases of ocular choroidal malignant melanoma, wherein FDG PET-CT scan did not show as good uptake as seen in other cancers.